Detection of Tritrichomonas foetus by RT-rtPCR in pooled bovine preputial washings. (March 2023) - Schroeder, Megan E.; Meza, Denisse; Shah, Rohan; Leyva-Baca, Ivan; Conrad, Rick; Ferro, Pamela J.
Trichomonosis is a venereal disease of cattle caused by the protozoan Tritrichomonas foetus. T. foetus infection in cattle herds can be economically costly for cattle producers; therefore, testing is important for detection of the agent. Given that bulls are considered to be subclinical carriers of T. foetus, it is important to detect T. foetus infection prior to movement and/or breeding season. We have described previously the development of an updated set of PCR primers and probes that offer increased sensitivity of T. foetus detection in preputial washings collected in PBS by utilizing reverse-transcription real-time PCR (RT-rtPCR) that targets the 5.8S ribosomal RNA of the T. foetus organism. Here, we report improvements in the updated RT-rtPCR reagents as well as the evaluation of testing of pooled preputial washings. We found that up to 5 preputial washings can be pooled, similar to routine testing practices (InPouch culture), without reducing the sensitivity of detection of T. foetus.